The international protection of language rights - Paleker, Mohamed (Centre for Law and Society, 2024)
Speakers of more than six thousand languages are not entitled to education, nor to the administration of justice or public services through the medium of their mother tongue(s). This statement is true of most indigenous language minorities and universally of migrant, immigrant or refugee minorities. Many minority language groups are punished for speaking their mother tongue, both physically as well as psychologically and economically. While the overwhelming majority of minority language groups remain at the cutting edge of linguistic discrimination, some national and regional minorities (e.g. in Belgium, Canada, Finland, India, and Switzerland) by contrast, are empowered to exercise at least some of their basic linguistic rights.